Physiological and psychophysical responses of male soldiers to changes in marching gradient, speed and load - Todd, Andrew Ivan (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2002)
The present study sought to investigate the effects of changes in gradient, under apparently optimal combinations of speed and load, on selected physiological, psychophysical and biophysical responses of military personnel. Subjects (n = 32) were required to march under level (0%), downhill (-10%) and uphill (+10%) conditions. Under each gradient, subjects marched with the following speed-load combinations: 4 km.h-1 carrying 50 kg, 5 km.h-1 carrying 35 kg and 6 km.h-1 carrying 20 kg, a total of nine experimental conditions. Subjects were required to march for six minutes under each condition. Physiological responses (HR, VO2, R, Br, VE, VT, EE) indicated that subjects were not overly taxed by the three speed-load combinations during level marching, which elicited submaximal demands. Furthermore, the results revealed that downhill marching with heavy loads results in similar responses to level marching, while lighter loads may result in significant reductions in physical demands compared to level marching. The physiological responses to uphill marching revealed that subjects were severely physically taxed under these conditions, regardless of speed-load combination. It is unlikely that soldiers would be able to maintain these intensities for an extended period without undue fatigue. It is evident from the psychophysical responses (Rating of Perceived Exertion and Body Discomfort) that subjects perceived the heavy load conditions, regardless of gradient, to be the most stressful on the cardiovascular and muscular systems. The positive gradient conditions also elicited elevated RPE and Body Discomfort responses, while lighter load downhill conditions were perceived to result in the least strain.
Keywords: Soldiers -- South Africa -- Physiology; South Africa Army -- Physical training; Marching -- Physiological aspects; Psychophysiology